Modified Anterior Craniofacial Osteotomy Using Partial Nasal Bone Division and Reconstruction in Frontoethmoidal Sinus Meningioma - Park, Eon Ju; Kim, Hong Il; Park, Jin Hyung; Yi, Hyung Suk (Archives of craniofacial surgery, 2017)
Typical transcranial approaches are insufficient for adequate visualization and resection of skull base tumors. Different approaches with multiple modifications have been attempted. Here, we describe a new approach for a lesion that is central and hard to treat by conventional craniotomy and successful reconstruction with calvarial bone graft and titanium mesh plate. A 69-year-old female patient presented with recurrent meningioma. The tumor had invaded the frontal lobe, right supraorbital rim, and ethmoidal bone. We performed a modified anterior craniofacial approach that fully exposed the tumor and invaded bone. In consideration of the patient's age and cosmetic result, the tumor and invaded bone was resected and the defect area was reconstructed with titanium mesh and calvarial bone graft. At 6 months postoperative the patient had no complications and was satisfied with the esthetic result. We report this case to demonstrate the successful approach and reconstruction using this technique.